Deskripsi ketinggian korpus mandibula melalui arsip radiografi digital panoramik pada pasien di RSGM Unpad - Icha Putri; Ria Noerianingsih Firman; Moch Rodian (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: The purpose of this study is to obtain measurements of dentate and edentulous corpus mandibulae height on RSGM Unpad patients through digital panoramic radiograph. Material and Methods: This research is using descriptive method. Population in this research is digital panoramic radiograph from RSGM Unpad patient’s database. The technique used is purposive sampling, and obtained 50 panoramic digital panoramic radiograph samples. Results: The results shows the highest dentate corpus mandibulae height is in men 38,1 mm age 65-85 on left side of corpus and the highest edentulous corpus mandibulae height is in men 26,3 mm age 55-64 on right side of corpus. Conclusion: To summarize, the highest dentate corpus mandibulae height on the right side is in men age 45-54, on the left side is in men age 65-85, the highest edentulous corpus mandibulae on the right and left side is in men age 55-64, and overall corpus mandibulae height on the right and left side on women is lower than men in all ages.